Réponses

Meilleure réponse !
2014-05-27T21:38:18+02:00
a) 4(x+5) = 10x+3
4x+20 = 10x+3
20-3 = 10x-4x
17 = 6x
x = 17/6
b) 3(x-2) = 6(x+4)
3x-6 = 6x+24
-30 = 3x
x= -30/3 = -10
c) 7x-(5x+3) = 5(x-3)+2
7x-5x-3 = 5x-15+2
-3+15-2 = 5x-7x+5x
10 = 3x
x = 10/3
d) 7(n+2)-3 = 25-(3n+4)
7n+14-3 = 25-3n-4
7n+3n=25-4-14+3
10n = 10
n=10/10
n=1
e) 4y+3(4y-2) = 3(y+1)
4y+12y-6 = 3y+3
13y = 9
y = 9/13
2014-05-27T21:51:12+02:00
a) 4(x+5) = 10x+3 
4x+20 = 10x+3 
20-3 = 10x-4x 
17 = 6x 
x = 17/6 
b) 3(x-2) = 6(x+4) 
3x-6 = 6x+24 
-30 = 3x 
x= -30/3 = -10 
c) 7x-(5x+3) = 5(x-3)+2 
7x-5x-3 = 5x-15+2 
-3+15-2 = 5x-7x+5x 
10 = 3x 
x = 10/3 
d) 7(n+2)-3 = 25-(3n+4) 
7n+14-3 = 25-3n-4 
7n+3n=25-4-14+3 
10n = 10 
n=10/10 
n=1 
e) 4y+3(4y-2) = 3(y+1) 
4y+12y-6 = 3y+3 
13y = 9 
y = 9/13